The financial position of Irish railways - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1867)
Mr. William John Hancock exhibited the following Tables, compiled by Dr. Hancock, to shew the financial position of Irish Railways, and explained the views of Dr. Hancock in respect of the statistics thus shown. It appears from these tables that at present there are in Ireland three railways bankrupt, or winding-up; two at a stand-still; six paying no dividend on the preference stock; ten paying no dividend on the ordinary shares; seven, the dividends of which were less than those paid on the Government Funds; six paying dividends at a rate less than that of commercial interest; and but one the shares of which were above par.
Read Tuesday, 24th April, 1866
Keywords: Railway infrastructure; Railway finances; 314.15